A Inquisição nas Minas: os Cadernos do Promotor no Episcopado de Dom Frei Manuel da Cruz (1745-1764) - Isabela de Andrade Pena Miranda Corby (2015)
The present dissertation studies the Prosecutor's Books and some of its complaints - aiming to comprehend the proceedings of the Inquisition in colonial Minas Gerais during the episcopate of Dom Manoel da Cruz (1745-1764). This incursion on the Inquisition world visits historiographic papers on the theme, the Regiment of The Holy Office from 1640, letters from Dom Frei Manoel da Cruz and the complaints on the Books - documents that raises a scenery marked by the most varied actors and groups, followed by its interests and tensions. The Bishopric of Mariana, by the optics of D. Frei Manoel da Cruz, and the Court's proceedings will be the conductors, instrumentalizing the perception on how the colonial population used to interact with the agents and procedures of The Holy Office. Lastly, the paper utilizes the micro history methodology to enter the History of Law, seeking to apprehend connections and evidences that transcends the motivating objectives of the Prosecutor's Books complaints. The research concludes that the study of inquisitional sources reveals itself important and necessary to understand the consolidation of legal institutes that still remains in the legislation, as well as formalities and rituals of the judicial power.